Effect of dopant on ion-dynamics of sodium ion-based flexible polyblend electrolyte for electrochemical device application - Cyriac, Vipin; Ismayil; Sudhakar, Y.N.; Mishra, Kuldeep; Rojudi, Z.E.; Murari, M.S.; Noor, I.M. (Elsevier Ltd, 2024)
This work examines the impact of NaNO3 salt on a NaAlg: PVA blend polymer, focusing on charge carrier properties, such as number density (n), mobility (μ), and diffusion coefficient (D). It is found that the addition of NaNO3 increased the room temperature conductivity from (6.12±0.15) × 10−8 S cm−1 (PNN0, salt-free) to (6.50±0.03) × 10−6 S cm−1 (PNN15, 15 wt. NaNO3), influenced by increasing n compared to µ. Temperature-dependent conductivity revealed a significant influence of both n and μ on electrolyte conductivity, and the ion dynamics were explored using various formalisms. XRD studies showed reduced crystallinity owing to the interaction of Na+ and NO3− with -OH groups, as confirmed by IR spectroscopy. Scanning electron microscopy confirmed salt deposits at higher concentrations. However, sufficient mechanical strength was observed for the optimally conducting sample. Obtained results showed the potential applications of the sample in electrochemical devices.